Let's Read Media in Indonesian Language Learning to Improve Reading Literacy of Grade 1 Students - Nur Samsiyah; Agung Widyantoro (Nexus Publishing NXP, 2025)
The development of technology has an impact on the use of increasingly advanced media, especially digital media. Media becomes a supporter in literacy learning in elementary schools for grade 1, one of which is Let's read media. This study aims to determine the use of Let's read media in learning Indonesian to improve reading literacy of grade 1 elementary school students. This study is a descriptive qualitative study. The subjects of the study were teachers and grade 1 students at Bulu 03 Pilangkenceng Elementary School. The number of students was 15. Data collection techniques were carried out by performance, tests and observations. The data collection instrument used a reading test to measure students' reading abilities, and an observation sheet to see students' reading literacy activities and learning activities using let's read media. Data analysis used Milles and Huberman which consisted of reduction, presentation and drawing conclusions. The results of the study showed that students' reading performance had a very good category as shown by their appearance and reading skills. The results of the observation showed that students' activity in using let's read media was very high, seen from their activeness and cooperation in compiling stories and notes on titles and readings that they had written. It is hoped that by using the Let's Read media, students will be more active in learning not only in Indonesian language lessons but also other lessons and can be used by other teachers in different classes.